Effect of packing in the airflow passage on the performance of a solar air-heater with conical concentrator - Togrul, IT; Pehlivan, D (Pergamon-Elsevier Science Ltd, 2005)
In this work, a selective absorbing surface and packing in the two-pass airflow passage of the absorbing tube were used and their effects on the efficiencies of a new solar air heater with a conical concentrator tracking the sun from sunrise to sunset were investigated. Aluminium wire mesh with a variety of folding number was tested as the packing material. The results were compared to those obtained with empty absorbing tube. Beside these, various aspects of the heat and fluid flow in the absorbing tube as influencing the system performance were searched by evaluating friction factors, pumping power, convective heat transfer coefficients and Colburn factors for empty and packed airflow passage of the absorbing tube. Although, incorporation independently of selective surface or packing material resulted the efficiency of the system to increase considerably, the highest efficiencies were obtained by using both. It was found that the airside heat transfer coefficient has been about 26W/m(2)K for empty airflow passage of the absorbing tube. By using aluminium wire mesh packing, the heat transfer coefficient increased regularly with increasing number of folds of the wire mesh packing and reached to 240W/m(2)K in the case of 14 folds. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: conical concentrator; solar air heater; selective surface; packing; heat transfer